Marketing Strategy Using SWOT Analysis to Increase Sales of Amanah Products (Case Study at PT. Pegadaian UPS Simpang Lima Banyuwangi) - Nur Hafidoturrohmah; Imam Muslih (Journal of Business Improvement, 2025)
This study aims to analyze the marketing strategy of the Amanah product at PT. Pegadaian UPS Simpang Lima Banyuwangi using SWOT analysis. As one of the company's main products, Amanah offers vehicle financing for micro-entrepreneurs, employees, and professionals with low administrative costs and fixed installments. Despite these advantages, the market performance of the Amanah product faces challenges, such as low public awareness and competition from other financial institutions offering similar products. Using a qualitative descriptive approach, this study identifies the strengths, weaknesses, opportunities, and threats of the Amanah product. The findings indicate that the Amanah product benefits from PT. Pegadaian's strong reputation, extensive branch network, and flexible financing options. However, the study also highlights areas for improvement, such as enhancing digital promotion and offering more competitive down payment requirements. This SWOT analysis provides strategic recommendations to strengthen public awareness of the product, align services with customer needs, and expand the customer base